The relationship between students’ involvement in 21st century classroom learning activities and higher order thinking skills - Irwan Fariza Sidik; Mohd Mahzan Awang; Abdul Razaq Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2019)
The implementation of the 21st century learning among students was introduced through the Malaysian Education Development Plan (MEDP) 2013-2025. Researches suggest that students’ involvement in 21st century learning activities in the classroom is related to the development of higher order thinking skills. This study was conducted to identify the level and relationship of students’ involvement in the implementation of 21st century learning in the classroom and the students’ higher order thinking skills. This study is a cross-sectional survey that uses questionnaires to collect data. Cluster sampling was used to choose a total of 200 Form Four students in Negeri Sembilan. Descriptive and inferential (Pearson Correlation) statistics were used to analyze the data. The findings show that students’ involvement in 21st century classroom learning activities and their higher order thinking skills are at a moderate level. It was also found that there is a significant relationship between students’ involvement in 21st century learning activities in the classroom with their levels of higher order thinking skills. The findings imply that students need to have a high level of readiness to ensure a successful implementation of 21st century learning in the classroom, which would contribute to their development of higher order thinking skills.